ANALISIS KINERJA PEMBANGKIT LISTRIK HYBRID PLTS–MIKROHIDRO SKALA KECIL 500 W SEBAGAI PENERANGAN JALAN UMUM BAGI PETANI DI KELURAHAN TARATARA, KOTA TOMOHON - Supit, Marcelino Sanio; Makal, Johan F.; Bijang, Nathaniel Lumalan (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
The lack of public street lighting (PJU) in remote farming areas around Tomohon City forces farmers to walk through plantation roads in the dark, raising both safety and productivity concerns during after-hours activities. This study analyzes the performance of a small-scale 500 W hybrid power system that combines solar photovoltaic (PV) and microhydro generation to supply street lighting for farmers in Taratara Village, Tomohon. The system consists of a 400 Wp monocrystalline PV array, a 500 W crossflow microhydro turbine with a permanent-magnet generator, a 24 V/100 Ah deep-cycle battery bank, an MPPT charge controller, a dump-load resistor, and DC/AC protection devices. Field testing was carried out for fourteen consecutive days, recording voltage, current, generated energy, battery state-of-charge, and load behaviour through an ESP32-based data logger. The PV subsystem delivered an average of 1.92 kWh/day at 14.76% conversion efficiency, while the microhydro turbine produced 8.71 kWh/day at 40.66% hydraulic-to-electrical efficiency. The combined hybrid output of 10.27 kWh/day comfortably covered the load demand of six 30 W LED lamps operating 12 hours nightly (2.16 kWh/day). The control and protection system kept battery SoC within 62-95% and successfully cleared all four simulated fault scenarios within 18-320 ms. The hybrid configuration is therefore considered technically reliable as an off-grid PJU solution for remote agricultural areas.